KAJIAN PENDIDIKAN DI MALUKU: ANALISIS KONDISI, TANTANGAN, DAN STRATEGI PENGEMBANGAN PENDIDIKAN DI KOTA AMBON - Grace Lisapaly; Tanwey Gerson Ratumanan; Theresia Laurens (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the state of education in Ambon City as part of the development of education in Maluku Province, and to identify various challenges affecting the implementation of education. The study employed a qualitative approach with a literature review method utilizing various scientific sources, policy documents, government reports, and educational statistics. The analysis was conducted to obtain a comprehensive picture of access, quality, equity, and governance of education in Ambon City. The results of the study indicate that Ambon City has significant potential for educational development through the existence of diverse educational institutions, local government support, and community participation in supporting the educational process. Nevertheless, various challenges remain, including disparities in educational quality, limited facilities and infrastructure in some educational units, the need to improve the competency of teaching staff, and the suboptimal use of learning technology. To address these challenges, an educational development strategy is needed that includes strengthening educational governance, enhancing teacher professionalism, developing educational infrastructure, utilizing information technology in learning, and increasing collaboration between the government, schools, and the community. This strategy is expected to support the realization of a quality, inclusive, competitive, and sustainable education system in Ambon City.